Thermal behaviour of nicotinic acid, sodium nicotinate and its compounds with some bivalent transition metal ions - Nascimento, A. L. C. S. do [UNESP]; Caires, F. J. [UNESP]; Gomes, D. J. C. [UNESP]; Gigante, A. C. [UNESP]; Ionashiro, Massao [UNESP] (Elsevier B.V., 2014)
Solid-state M(L)(2)center dot nH(2)O compounds, where M stands for bivalent transition metals (Mn, Fe, Co, Ni, Cu and Zn), L is nicotinate and n = 0-4.5, have been synthesized. Characterization and thermal behaviour of these compounds were investigated employing elemental analysis based on the mass losses observed in the TG-DTA curves, complexometry, X-ray diffractometry, infrared spectroscopy (FTIR), simultaneous thermogravimetric and differential thermal analysis (TG-DTA) and TG-DSC coupled to FTIR. The thermal behaviour of nicotinic acid and its sodium salt was also investigated. For the hydrated transition metal compounds, the dehydration and thermal decomposition of the anhydrous compounds occur in a single step. For the sodium nicotinate, the final residue up to 765 degrees C is sodium carbonate and for the transition metal nicotinates, the final residues are Mn3O4, Fe2O3, Co3O4, NiO, CuO and ZnO. The results also provided information concerning the thermal stability, thermal decomposition and identification of the gaseous products evolved during the thermal decomposition of the compounds. (C) 2013 Published by Elsevier B.V.
Keywords: Bivalent transition metals; Nicotinate; Thermal behaviour